2014
DOI: 10.1159/000363215
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors as Causes for Hearing Impairment

Abstract: The purpose of this paper is to provide a contemporary review of the correlation between cardiovascular risk factors (CVRFs) and hearing impairment (HI). Weconducted a comprehensive review of the literature in order to assess the effects of the different CVRFs on HI. We focused on the pathological findings in the inner ear and their correlation with cochlear function in population-based studies. We found that CVRFs adversely affect hearing acuity. HI diagnosis should be accompanied by detecting and treating CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 33 publications
(32 reference statements)
1
31
0
2
Order By: Relevance
“…Several studies have suggested the risk factors for SSNHL include traditional cardiovascular risk factors, such as CAD, hypertension, chronic kidney disease, and DM (18,19). In our study, hypertensive patients with osteoporosis had borderline higher risk of SSNHL than hypertensive pa- tients without osteoporosis.…”
Section: Discussionsupporting
confidence: 46%
“…Several studies have suggested the risk factors for SSNHL include traditional cardiovascular risk factors, such as CAD, hypertension, chronic kidney disease, and DM (18,19). In our study, hypertensive patients with osteoporosis had borderline higher risk of SSNHL than hypertensive pa- tients without osteoporosis.…”
Section: Discussionsupporting
confidence: 46%
“…Rosen suggested the relationship between CVD and HL after identifying superior hearing in the southeast Sudanese Mabaan tribe, where CVD was less prevalent compared to similarly aged people in the United States . It is hypothesised that reduced blood supply to the stria vascularis of the cochlea due to CVD can lead to impairment of inner‐ear function, resulting in HL . Previous studies have found that cardiovascular‐related HL may be greater at lower frequencies (250‐2000 Hz) .…”
Section: Introductionmentioning
confidence: 99%
“…59,63,64 In addition, in a related topic not without controversy, there are mixed results regarding the impact of cardiovascular disease on hearing loss. [65][66][67][68][69] Since ASA is recommended for cardiovascular prophylaxis, 70,71 if there is a true association between cardiovascular disease and hearing loss, then ASA might be indirectly protective of hearing in some patients through preventive effects.…”
Section: Potential Protective Effects Of Asa On Hearingmentioning
confidence: 99%